Ecology and Criminology? Applying the tenets of procedural justice to environmental regulations - Maxwell, Sheila Royo (Criminology & criminal justice, 2022)
Criminologists are increasingly investigating the harmful intersections between humans and the natural environment, largely under the green criminology banner. However, most discourses have largely remained at the macro level and empirical tests are limited. The foci of research had been industry, state/national actors or policy discourses and not individuals responding to mandated environmental regulations. Individual actors are especially important in developing countries where environmental regulations can substantially impact citizens’ livelihood opportunities. This research uses the procedural justice framework to understand citizens’ responses to an environmental regulatory body. A team of local researchers conducted face-to-face interviews with citizens affected by environmental regulations in the Banahaw protected landscape in the north-central Philippines to assess their trust and cooperation with the regulatory body. Results demonstrated high reliability for the key procedural constructs of respect, impartiality, voice, and trustworthiness. Path analysis showed that impartiality and voice were significantly related to perceived trustworthiness of the regulatory body and impartiality is directly related to cooperation. The results provide evidence that criminological perspectives are useful in organizing the complex dynamics of laws, enforcement and behavior change that is inherent in environmental regulations.